2005
DOI: 10.1007/s00268-005-7852-7
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Capsule‐ and Nerve‐sparing Cystectomy in Organ‐confined Bladder Cancer: Preliminary Results

Abstract: We present a novel radical cystectomy technique that allows bladder cancer control while maintaining urinary continence and reducing the risk of erectile dysfunction by sparing the prostatic capsule and the neurovascular bundles. Between September 1997 and December 2002, 85 men were candidates for cystectomy; 32 were selected for a prostatic capsule- and seminal-sparing cystectomy with orthotopic urinary diversion. All patients had clinical organ-confined bladder cancer (cT1 to cT3a). One patient died of unrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 40 publications
0
10
0
3
Order By: Relevance
“…This is considerably lower than the rate for cystoprostatectomy series, and clearly indicates that prostatic involvement can be identified preoperatively (Table 2). 7,[13][14][15][16][17][18][19][20][21][22] Occult prostate cancer Coexistent prostate cancer exists in patients with invasive bladder cancer at approximately the same frequency as in normal men. The risk of prostate cancer incidence or mortality is not any higher in bladder cancer patients than in the normal population.…”
Section: Prostatic Involvement By Tccmentioning
confidence: 99%
See 1 more Smart Citation
“…This is considerably lower than the rate for cystoprostatectomy series, and clearly indicates that prostatic involvement can be identified preoperatively (Table 2). 7,[13][14][15][16][17][18][19][20][21][22] Occult prostate cancer Coexistent prostate cancer exists in patients with invasive bladder cancer at approximately the same frequency as in normal men. The risk of prostate cancer incidence or mortality is not any higher in bladder cancer patients than in the normal population.…”
Section: Prostatic Involvement By Tccmentioning
confidence: 99%
“…In contrast, synchronous or metachronous prostate cancer in prostate-sparing series, where patients were screened for pre-existing prostate cancer, occurs in 2% to 4% (Table 2). 7,[13][14][15][16][17][18][19][20][21][22] Occasionally, even with this thorough screening, prostate cancer may develop. Vallancien and colleagues found that 3 of 100 men developed prostate cancer postoperatively.…”
Section: Prostatic Involvement By Tccmentioning
confidence: 99%
“…The continence rate for prostatesparing cystectomy in most series is excellent. [4][5][6][21][22][23][24][25][26][27] Of 10 series, 9 reported daytime continence rates of at least 94%. Nighttime continence rates were at least 94% in 6 series and all but 1 reported rates greater than 77%.…”
Section: Oncological Outcomesmentioning
confidence: 99%
“…In einer aktuellen klinischen Serie haben Gakis et al [11] Werden die klassischen Screeninguntersuchungen (DRE, TRUS, PSA) vor rZx angewendet, kann die Rate von synchronen oder sich metachron entwickelnden Prostatakarzinomen auf 2-4% reduziert werden. In den bisher publizierten klinischen Serien zur pZx mit 369 Patienten entwickelte sich ein in der über-wiegenden Mehrzahl kleinvolumiges und günstig differenziertes, organbegrenztes Prostatakarzinom in lediglich 12 (3%) Patienten [9,12,13,14,15,16,17,18,19,20,21,22,23].…”
Section: Begleitendes Prostatakarzinomunclassified
“…7 Werden die Patienten mit einer Tumorlokalisation am Blasenhals von der Indikationsstellung zur pZx ausgeschlossen, reduziert sich das Risiko einer Prostatabeteiligung auf 0-4% [9,12,13,14,15,16,17,18,19,20,21,22]. Bei den übrigen Patienten gilt es durch eine geeignete prä-operative oder intraoperative Diagnostik eine oberflächliche Beteiligung (muköse, duktale oder azinäre Invasion) von einer invasiven Beteiligung zu differenzieren.…”
Section: Urothelkarzinom Der Prostatischen Harnröhreunclassified